Green Advertising and Green Product Innovation Driving Green Purchase Behavior: The Mediating Role of Green Brand Awareness Among Generation Z in Indonesia - Arif Triwinarso; Annida Khoiriani (Universitas KH. Abdul Chalim Mojokerto, 2026)
Environmental sustainability has become a central concern in contemporary consumer behavior research, particularly among younger generations who demonstrate higher environmental awareness. Despite the growing interest in green consumption, the determinants of green purchase behavior remain insufficiently explored in developing country contexts. Prior studies have largely focused on consumer attitudes or purchase intentions, with limited attention to the role of marketing communication and product innovation in shaping environmentally responsible behavior. This study aims to examine how green advertising and green product innovation influence green purchase behavior through the mediating role of green brand awareness among Generation Z in Indonesia. The research adopts the Theory of Planned Behavior (TPB) as the primary theoretical framework to explain environmentally friendly purchasing behavior. A quantitative survey was conducted with 381 Generation Z consumers in Indonesia using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with AMOS.n The findings reveal that green advertising and green product innovation significantly influence green brand awareness and green purchase behavior. Green brand awareness also acts as a significant mediating variable that strengthens the relationship between marketing strategies and consumer purchasing behavior. Theoretically, this study extends the Theory of Planned Behavior by integrating green marketing communication and green product innovation as key antecedents of sustainable consumption behavior. Practically, the results suggest that companies targeting Generation Z should strengthen green communication strategies, invest in eco-friendly product innovations, and build strong green brand identities to encourage sustainable purchasing behavior.